Characterization and isomorphism conditions of cayley digraphs of some completely regular semigroups - John Meksawang (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
In this thesis, we characterize directed graphs which are Cayley digraphs of com- pletely simple semigroups. Moreover, we investigate the isomophism conditions for Cayley digraphs of a rectangular group, and for Cayley digraphs of Brandt semigroups.